On cost tradeoffs between conservative and market value accounting - WEYNS, Guy Joseph Mathilde (Institutional Knowledge at Singapore Management University, 1997)
We identify a cost tradeoff relevant to the comparison of alternative accounting regimes. We compare equilibrium deadweight losses, due to transacting and auditing, across the historical cost, lower-of-cost-or-market, and market value regimes. We provide conditions for each of the regimes to dominate the other two. We show that while market-value accounting is likely to prevail in an inflationary setting, it may also be optimal under deflation. Similarly, lower-of-cost-or-market is likely to prevail in a deflationary setting, though it may also be optimal under inflation. Last, historical cost prevails only if the variation in asset prices is sufficiently high.